Conductive inks containing carbon nanostructures
Patent Information
- Application Number
- JP2024544424
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-28
- Filing Date
- 2023-01-24
- Publication Date
- 2025-02-21
Smart Images

Figure 2025505122000001_ABST
Abstract
Description
[Technical Field]
[0001] 1. Field of the Invention The present invention relates to electrically and thermally conductive inks containing carbon nanostructures. [Background technology]
[0002] 2. Description of Related Technology Conductive inks have been employed for decades to print conductors, resistors, and sensors in electronics and devices. Conductive inks can be printed onto flexible polymer-based substrates or fused into solid substrates such as glass windows. One interesting application of conductive inks is printing heating elements that can be used in a variety of applications, including heated floors, windows, and walls, clothing and household items (e.g., appliances and coffee mugs), and automobiles. Conductive inks for this application contain silver- or carbon-based conductive fillers (e.g., graphite, carbon black). While the use of silver is effective in providing a conductive path, it is not an economical approach. Without proper design of the heating element and circuitry, the silver ink can overheat, distorting the polymer substrate and raising safety concerns. While graphite and carbon black can be used as heating resistors, their heating rates and peak temperatures have been found to be insufficient for certain applications requiring higher performance. Therefore, it would be desirable to have a conductive ink formulation that is more economical than 100% silver solutions, yet offers improved performance compared to graphite and carbon black. Summary of the Invention
[0003] In one embodiment, the conductive ink comprises 0.05% to 30% by weight (dry basis), e.g., 0.1% to 20% by weight, 0.5% to 10% by weight, or 0.75% to 5% by weight, of at least one CNS-derived material selected from the group consisting of carbon nanostructures, carbon nanostructure fragments, and crushed carbon nanotubes, and a binder in a liquid vehicle. For example, the ink may comprise 0.01% to 10% by weight, e.g., 0.05% to 9% by weight, 0.1% to 8% by weight, 0.5% to 7% by weight, or 1% to 5% by weight of the CNS-derived material, based on the total weight of the conductive ink. The liquid vehicle may comprise an organic solvent, water, or both. The binder may comprise a polymer, a monomer, an oligomer, or a blend of two or more thereof.
[0004] In any of these embodiments, the conductive ink may further include a dispersant, such as a nonionic dispersant, an anionic dispersant, or a cationic dispersant. Alternatively or additionally, the conductive ink may further include one or more additives selected from conductive additives, stabilizers, antioxidants, adhesion promoters, and viscosity modifiers. The additive may be a conductive additive selected from silver, copper, gold, platinum, palladium, ruthenium, copper, nickel, zinc, and conductive oxides. The conductive additive may be in the form of spheres, flakes, rods, or wires. The conductive additive may be present in an amount of 0 to 99% by weight on a dry basis, such as 1% to 90% by weight, 5% to 80% by weight, 10% to 70% by weight, 20% to 60% by weight, 30% to 50% by weight, 40% to 75% by weight, or 50% to 95% by weight.
[0005] In any of these embodiments, when the conductive ink is screen printed and cured, the resulting coating has a resistivity of at least 300 Ω / cm2 under an applied voltage of 40 V. °F (149°C). Alternatively or additionally, the conductive ink may contain up to 85% (dry basis), e.g., 65% to 83% metallic particulate, and when screen printed and cured, the resulting coating may have a lower surface resistivity than a coating having the same composition but without the CNS-derived material.
[0006] A substrate can have a conductive ink according to any of these embodiments printed and cured thereon. The cured ink can have a thickness of 0.1 microns to 100 microns, e.g., 0.5 microns to 80 microns, 1 micron to 50 microns, 5 microns to 30 microns, 10 microns to 70 microns, 30 microns to 60 microns, or 50 microns to 90 microns. -6 ~10 14 ohm·cm, e.g., 10 -5 ~5×10 13 , 10 -4 ~10 13 , 10 -3 ~5×10 12 , 10 -2 ~10 12 , 0.1 to 5 × 10 11 ohm·cm, 1 to 10 6 ohm·com, at most 0.1 ohm·cm, at most 1 ohm·cm, at most 10 ohm·cm, at most 100 ohm·cm, at most 10 4 ohm·cm, at most 10 6 ohm·cm, 10 6 ~10 10 ohm.com, 10 10 ~10 12 ohm·cm, or 10 12 ~10 14 The cured ink may have a volume resistivity of 10 ohm-cm. -6 ~10 14 Ohms / sq, e.g., 10 -5 ~5×10 13 , 10 -4 ~10 13 , 10 -3 ~5×10 12 , 10 -2 ~1012 , 0.1 to 5 × 10 11 Ohms / sq, 1-10 6 ohms·com, at most 0.1 ohms / sq, at most 1 ohm / sq, at most 10 ohms / sq, at most 100 ohms / sq, at most 10 4 ohms / sq, at most 10 6 Ohms / sq, 10 6 ~10 10 ohm.com, 10 10 ~10 12 ohms / sq or 10 12 ~10 14 It may have a surface resistivity of ohms / sq.
[0007] In any of these embodiments, the substrate can comprise fabric, paper, wood, metal, glass, ceramic, concrete, a polymer, or a mixture or composite of two or more thereof. For example, the substrate can comprise a polyolefin, a polyimide, a polyester, a polyurethane, or a vinyl polymer such as polyethylene, polyethylene terephthalate, polyvinyl chloride, or polystyrene. The substrate can be a film, a woven fabric, or a nonwoven fabric.
[0008] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are intended to provide further explanation of the invention as claimed.
[0009] The invention will now be described with reference to the several figures of the drawing. [Brief explanation of the drawings]
[0010] [Figure 1A] FIG. 1 illustrates the difference between Y-shaped MWCNTs (FIG. 1A), which are not carbon nanostructures or derived therefrom, and branched MWCNTs (FIG. 1B), which are carbon nanostructures. [Figure 1B] FIG. 1 illustrates the difference between Y-shaped MWCNTs (FIG. 1A), which are not carbon nanostructures or derived therefrom, and branched MWCNTs (FIG. 1B), which are carbon nanostructures. [Figure 2A] TEM images showing the characteristic features of multi-walled carbon nanotubes found in carbon nanostructures. [Figure 2B] TEM images showing the characteristic features of multi-walled carbon nanotubes found in carbon nanostructures. [Figure 3A] FIG. 1 is an illustration of carbon nanostructure flake material after isolation of the carbon nanostructures from the growth substrate. [Figure 3B] 1 is an SEM image of exemplary carbon nanostructures obtained as flake material. [Figure 4] 1 is an optical micrograph of a printing ink formulation according to an exemplary embodiment (scale bar=1 mm). [Figure 5A] FIG. 1 is a schematic diagram showing the formation of a heating element for use in conductive ink testing. [Figure 5B] FIG. 1 is a schematic diagram showing the formation of a heating element for use in conductive ink testing. [Figure 5C] FIG. 1 is a schematic diagram showing the formation of a heating element for use in conductive ink testing. DETAILED DESCRIPTION OF THE INVENTION
[0011] The conductive ink comprises 0.05% to 30% by weight (dry basis) carbon nanostructures and a binder in a liquid vehicle. In one embodiment, the conductive ink is used in an electrothermal heater. The conductive ink is printed onto a substrate to create heater stripes, such as in a crosshatched pattern or other suitable pattern. The heater stripes can be connected to a power source, such as a battery, using low-resistance traces formed from high-conductivity ink, metal wire, or other trace materials known to those skilled in the art. Depending on the size of the heater, it may be desirable to have one or more conductive buses that distribute voltage to the various heater stripes. The power source is in electrical communication with the heater stripes via the low-resistance traces and any conductive buses. All of these components can be deposited by any technique known to those skilled in the art, such as screen printing, bubble jet printing, electrohydrodynamic printing, inkjet printing, or aerosol jet printing. The conductive inks disclosed herein can be deposited as a single layer (i.e., in a single printing pass) or in two or more layers. The additional layers may increase the thickness and decrease the resistivity of the printed and cured ink. If an ink is used, it may be cured by air drying, heat, UV exposure, infrared exposure, chemical methods, or other methods known to those skilled in the art.
[0012] The substrate can be any suitable rigid or flexible material. Fabric, paper, wood, metal, glass, ceramic, concrete, plastic, and / or other polymers or composites can be used. Suitable polymers include polyolefins such as polyethylene, polyimides, polyesters such as polyethylene terephthalate, polyurethanes, vinyl polymers such as polyvinyl chloride, polystyrene, and polyesters. Of course, any of these polymers can be used as a film, as a woven or nonwoven fabric, or as a rigid bulk. Non-conductive substrates may be preferred to better control the electrical conduction path through the heater.
[0013] The electric heater may be configured in any manner known to those skilled in the art, one exemplary configuration being described in U.S. Patent No. 20200396797, the entire contents of which are incorporated herein by reference.
[0014] The conductive ink comprises carbon nanostructures (CNS) and / or CNS-derived materials (e.g., CNS, CNS fragments, or crushed CNTs). As known in the art, carbon nanotubes (CNTs or CNTs in plural) are composed of sp nanotubes connected to each other to form a honeycomb lattice that forms cylindrical or tubular structures. 2 Carbon nanotubes are carbonaceous materials containing at least one sheet of hybridized carbon atoms. Carbon nanotubes can be single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs). SWCNTs are sp 2 They can be considered hybridized carbon allotropes. Their structure is a cylindrical tube containing six-membered carbon rings, whereas the analogous MWCNTs have several tubes of concentric cylinders. The number of these concentric walls can vary, for example, from 2 to 25 or more. Typically, the diameter of an MWNT can be 10 nm or more, whereas a typical SWNT is 0.7 to 2.0 nm.
[0015] In many of the CNSs used in various embodiments, the CNTs are MWCNTs, e.g., having at least two coaxial carbon nanotubes. The number of walls present may be on the order of 2-30, e.g., 4-30, 6-30, 8-30, 10-30, 12-30, 14-30, 16-30, 18-30, 20-30, 22-30, 24-30, 26-30, 28-30, or 2-28, 4-28, 6-28, 8-30, or 9-30, as determined, e.g., by transmission electron microscopy (TEM) at a magnification sufficient to analyze the number of walls in a particular case. 28, 10-28, 12-28, 14-28, 16-28, 18-28, 20-28, 22-28, 24-28, 26-28, or 2-26, 4-26, 6-26, 8-26, 10-26, 12-26, 14-26, 16-26, 18-26, 20-26, 22-26, 24-26, or 2-24, 4-24, 6-24, 8-24, 10-24, 12-24, 14-24, 16- 24, 18-24, 20-24, 22-24, or 2-22, 4-22, 6-22, 8-22, 10-22, 12-22, 14-22, 16-22, 18-22, 20-22, or 2-20, 4-20, 6-20, 8-20, 10-20, 12-20, 14-20, 16-20, 18-20, or 2-18, 4-18, 6-18, 8-18, 10-18, 12-18, 14-18 , 16-18, or 2-16, 4-16, 6-16, 8-16, 10-16, 12-16, 14-16, or 2-14, 4-14, 6-14, 8-14, 10-14, 12-14, or 2-12, 4-12, 6-12, 8-12, 10-12, or 2-10, 4-10, 6-10, 8-10, or 2-8, 4-8, 6-8, or 2-6, 4-6, or 2-4.
[0016] Because CNSs are polymeric, highly branched, cross-linked networks of CNTs, at least some of the chemistry observed in individualized CNTs can also occur in CNSs. Additionally, several attractive properties often associated with the use of CNTs are also found in materials incorporating CNSs. These include, for example, electrical conductivity, attractive physical properties such as maintaining or enabling good tensile strength when integrated into silicone-based compositions, thermal stability (sometimes comparable to that of diamond crystals or in-plane graphite sheets), and / or chemical stability, to name a few.
[0017] However, as used herein, the term "CNS" is not synonymous with individualized, non-entangled structures such as "monomeric" fullerenes (the term "fullerene" broadly refers to hollow spheres, ellipsoids, tubes, e.g., carbon nanotube forms, and other shaped allotropes of carbon). Indeed, many embodiments of the present invention highlight the differences and advantages observed or anticipated in the use of CNSs as opposed to their CNT building blocks. While not wishing to be bound by any particular interpretation, it is believed that the combination of branching, cross-linking, and wall sharing between carbon nanotubes in a CNS reduces or minimizes van der Waals forces that are often problematic when using individual carbon nanotubes as well, particularly when it is desired to prevent agglomeration.
[0018] In addition to or as an alternative to performance attributes, CNTs that are part of or derived from a CNS can be characterized by several features, at least some of which may be relied upon to distinguish them from other nanomaterials, such as conventional CNTs (i.e., CNTs that are not derived from a CNS but are individualized, pristine, or available as fresh CNTs).
[0019] In many cases, CNTs present in or derived from CNSs have a typical diameter of 100 nanometers (nm) or less, for example, in the range of about 5 to about 100 nm, such as in the range of about 10 to about 75, about 10 to about 50, about 10 to about 30, or about 10 to about 20 nm.
[0020] In specific embodiments, at least one of the CNTs has a length of 2 microns or greater as determined by SEM. For example, at least one of the CNTs will have a length in the range of 2-2.25 microns, 2-2.5 microns, 2-2.75 microns, 2-3.0 microns, 2-3.5 microns, 2-4.0 microns, or 2.25-2.5 microns, 2.25-2.75 microns, 2.25-3 microns, 2.25-3.5 microns, 2.25-4 microns, or 2.5-2.75 microns, 2.5-3 microns, 2.5-3.5 microns, 2.5-4 microns, or 3-3.5 microns, 3-4 microns, 3.5-4 microns, or greater. In some embodiments, two or more, e.g., a portion, e.g., at least about 0.1%, at least about 1%, at least about 10%, at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, or even more than half, of the CNTs may have lengths greater than 2 microns, e.g., within the ranges specified above, as determined by SEM.
[0021] Many of the CNTs in a CNS share at least a portion of their CNT sidewalls with another CNT. It is generally understood that not every carbon nanotube in a CNS necessarily needs to be branched, bridged, or share a common wall with another CNT, but at least a portion of the CNTs in a carbon nanostructure can be interdigitated with each other and / or with branched, bridged, or common-wall carbon nanotubes in the remainder of the carbon nanostructure.
[0022] The morphology of CNTs present in CNSs, CNS fragments, or CNS-derived crushed CNTs is often characterized by a high aspect ratio, typically having a length greater than 100 times its diameter, and in certain cases may be significantly longer. For example, in a CNS (or CNS fragment), the length-to-diameter aspect ratio of CNTs may be about 200 to about 1000, e.g., 200-300, 200-400, 200-500, 200-600, 200-700, 200-800, 200-900, or 300-400, 300-500, 300-600, 300-700, 300-800, 300-900, 300-1000, or 400-500, 400-500, 400-600, 400-700, 400-800, 400-900, 400-900, 400-1000, 400-2000, 400-2000, 400-3000, 400-400, 400-500, 400-600, 400-500, 400-600, 400-700, 400-800, 400-900, 400-1000, 400-2000, 400-3000, 400-400, 400-500, 400-600, 400-500, 400-600, 400-700, 400-800, 400-90 or 600 to 700, 600 to 800, 600 to 900, 600 to 1000, 700 to 800, 700 to 900, 700 to 1000, or 800 to 900, 800 to 1000, or 900 to 1000, or the like.
[0023] It has been found that in CNSs, and even in CNS-derived structures (CNS-derived materials, e.g., CNSs, CNS fragments, or crushed CNTs), at least one of the CNTs is characterized by a certain "branching density." As used herein, the term "branching" refers to the characteristic of a single carbon nanotube splitting into multiple (two or more) connected multi-walled carbon nanotubes. One embodiment has a branching density whereby there are at least two branches along a 2 micrometer length of the carbon nanostructure, as determined by SEM. More than two branches are also possible.
[0024] Additionally or alternatively, the number of walls observed in a branching region (point) in a CNS, CNS fragment, or crushed CNT differs between one side of the branch (e.g., before the branch point) and the other side of this region (e.g., after or past the branch point). Such a change in wall number, also referred to herein as "asymmetry" in the number of walls, is not observed in regular Y-shaped CNTs (where the same number of walls is observed in both the region before and the region past the branch point).
[0025] Diagrams illustrating these features are provided in Figures 1A and 1B. Shown in Figure 1A is an exemplary Y-shaped CNT 11 that is not derived from CNS. Y-shaped CNT 11 includes a catalyst particle 13 at or near branch point 15. Regions 17 and 19 are located before and after branch point 15, respectively. For a Y-shaped CNT such as Y-shaped CNT 11, both regions 17 and 19 are characterized by having the same number of walls, i.e., two walls in the figure.
[0026] In contrast, in the CNS (FIG. 1B), the CNT building block 111 that branches at branch point 115 does not contain a catalyst particle at or near this point, as seen in catalyst-devoid region 113. Furthermore, the number of walls present in region 117, located before, preceding (or on a first side of) branch point 115, differs from the number of walls present in region 119 (located past, following, or opposite branch point 115). More specifically, the three-wall feature found in region 117 does not continue into region 119 (which has only two walls in the view of FIG. 1B), causing the asymmetry discussed above.
[0027] These features are highlighted in the TEM images of Figures 2A and 2B.
[0028] More specifically, the CNS bifurcation in TEM region 40 of Figure 2A shows the absence of any catalyst particles. In the TEM of Figure 2B, first channel 50 and second channel 52 point out the asymmetry in the number of walls characterized by the bifurcated CNS, and arrow 54 points out the region displaying wall sharing.
[0029] One, more, or all of these attributes may be encountered in the coating compositions described herein.
[0030] In some embodiments, the CNSs exist as part of an entangled and / or interconnected network of CNSs, which can include bridges between CNSs.
[0031] Suitable CNS preparation techniques are described, for example, in U.S. Patent Application Publication No. 2014 / 0093728A1, published April 3, 2014, U.S. Patent Nos. 8,784,937B2, 9,005,755B2, 9,107,292B2, and 9,447,259B2, the entire contents of which are incorporated herein by reference.
[0032] As described in these documents, CNS can be grown on a suitable substrate, for example, on a catalyst-treated fiber material. The product can be a fiber-containing CNS material. In some cases, the CNS is separated from the substrate to form flakes.
[0033] As seen in U.S. Patent Application Publication No. 2014 / 0093728 A1, carbon nanostructures obtained as flake material (i.e., discrete particles with finite dimensions) exist as three-dimensional microstructures due to the entanglement and cross-linking of their highly aligned carbon nanotubes. The aligned morphology reflects the formation of carbon nanotubes on a growth substrate under rapid carbon nanotube growth conditions (e.g., several microns / second, e.g., about 2 microns / second to about 10 microns / second), resulting in substantially perpendicular carbon nanotube growth from the growth substrate. Without being bound by any theory or mechanism, it is believed that the rapid carbon nanotube growth rate on the growth substrate may contribute, at least in part, to the complex structural morphology of the carbon nanostructures. Additionally, the bulk density of CNSs can be altered to some extent by adjusting the carbon nanostructure growth conditions, including, for example, by varying the concentration of transition metal nanoparticle catalyst particles disposed on the growth substrate to initiate carbon nanotube growth.
[0034] The flakes can be further processed by cutting or fluffing (operations which may involve mechanical ball milling, grinding, blending, etc.), chemical processes, any combination thereof, etc.
[0035] In some embodiments, the utilized CNS is "coated," also referred to herein as "encapsulated" CNS. In a typical coating process, a coating is applied onto the CNTs that form the CNS. The coating process can form a partial or complete coating that is non-covalently bound to the CNTs and, in some cases, can act as a binder. Additionally or alternatively, a coating can be applied to an already formed CNS in a post-coating (or encapsulation) process. The binding coating allows the CNS to be formed into larger structures, granules, pellets, etc. In other embodiments, the granules or pellets are formed independently of the function of the coating.
[0036] For example, flake material can be captured and sprayed with an aqueous solution containing a binder (e.g., polyethylene glycol or polyurethane) to form wet flakes. The weight ratio of aqueous binder solution to flake material can be in the range of 8:1 to 15:1, e.g., 10:1 to 15:1, 10:1 to 13:1, or 10:1 to 12:1. The wet flakes can then be extruded to form a wet extrudate. Drying the wet extrudate (e.g., by air drying, oven drying) forms CNS pellets. Alternatively, drying the wet flakes forms CNS granules.
[0037] Various types of coatings can be selected. In many cases, sizing solutions commonly used to coat carbon or glass fibers can be used as coating materials for CNS. In such embodiments, the coating is in the range of about 0.1% to about 10% by weight, based on the total weight of the coated CNS material (e.g., by weight, about 0.1% to about 0.5%, about 0.5% to about 1%, about 1% to about 1.5%, about 1.5% to about 2%, about 2% to about 2.5%, about 2.5% to about 3%, about 3% to about 3.5%, about 3.5% to about 4%, about 4% to about The sizing agent is preferably 4.5%, about 4.5% to about 5%, about 5% to about 5.5%, about 5.5% to about 6%, about 6% to about 6.5%, about 6.5% to about 7%, about 7% to about 7.5%, about 7.5% to about 8%, about 8% to about 8.5%, about 8.5% to about 9%, about 9% to about 9.5%, or about 9.5% to about 10%. Specific examples of sizing materials include, but are not limited to, fluorine Examples of suitable binders include fluoropolymers such as poly(vinyldifluoroethylene) (PVDF), poly(vinyldifluoroethylene-co-hexafluoropropylene) (PVDF-HFP), poly(tetrafluoroethylene) (PTFE), polyimides, and water-soluble binders such as poly(ethylene) oxide, polyvinyl alcohol (PVA), cellulose, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), and copolymers and mixtures thereof. In many embodiments, the CNS used is treated with polyurethane (PU), thermoplastic polyurethane (TPU), or polyethylene glycol (PEG).In some cases, polymers such as epoxy, polyester, vinyl ester, polyetherimide, polyetherketoneketone, polyphthalamide, polyetherketone, polyetheretherketone, polyimide, phenol-formaldehyde, bismaleimide, acrylonitrile-butadiene styrene (ABS), polycarbonate, polyethyleneimine, polyurethane, polyvinyl chloride, polystyrene, polyolefin, polypropylene, polyethylene, polytetrafluoroethylene, elastomers such as polyisoprene, polybutadiene, butyl rubber, nitrile rubber, ethylene-vinyl acetate polymer, silicone polymer, fluorosilicone polymer, combinations thereof, or other polymers or polymeric blends can also be used as sizing materials. Conductive polymers such as polyaniline, polypyrrole, polythiophene, etc. can also be used to enhance electrical conductivity.
[0038] In an alternative implementation, a coating material may be utilized that can help stabilize CNS dispersions in aqueous or organic liquid vehicles. In one example, the coating is selected to facilitate and / or stabilize the dispersion of CNS and other CNS-derived materials in a vehicle formed by combining a desired coating resin with a desired vehicle, along with any dispersing agents. Any suitable combination of resin and vehicle as provided above may be employed. In another example, the coating material may be the same as, similar to, or compatible with a dispersant or thickener utilized in processing CNS. For example, CNS flake material may be coated with a dispersant suitable for use in the vehicle (e.g., organic or aqueous) system in which the CNS-polymer resin composition is dissolved / dispersed. In order to provide the appropriate amount of dispersant for a liquid dispersion or other formulation, it may be desirable to increase the amount of dispersant used in the coating material compared to the amount of coating used for CNS pellets or granules listed above for the sizing material. For example, based on the mass of the coated CNS material, the amount of dispersant can be at least 20% by weight, such as 25% to 60%, 30% to 55%, 40% to 50%, or 45% to 60%.
[0039] Exemplary dispersing agents include, but are not limited to, poly(vinylpyrrolidone), poly(vinylpyrrolidone-co-vinyl acetate), poly(vinyl butyral), poly(vinyl alcohol), polyalkylene oxides (e.g., polyethylene oxide or polypropylene oxide), polyalkylene oxides or acrylic polymers containing amine functionality, poly(propylene carbonate), cellulosic dispersing agents such as methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxymethyl cellulose, and hydroxypropyl cellulose, poly(carboxylic acids) such as poly(acrylic acid), polyacrylates, poly(methyl acrylate), poly(acrylamide), amide waxes, styrene maleic anhydride resins, amine-functionalized or amine-terminated compounds such as polyamines, tertiary amines, or quaternary ammonium-functionalized compounds such as tetraoctylammonium bromide, ethoxylates such as alkylphenol ethoxylates, e.g., octylphenol ethoxylate, or alkyl ethoxylates, multifunctional co-dispersing agents such as methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxymethyl cellulose, and hydroxypropyl cellulose. Examples include AMP™ dispersants, dispersants containing 2-amino-2-methyl-1-propanol, polyesters (e.g., polycaprolactone, polyvalerolactone, poly(hydroxystearic acid), or poly(hydroxyoleic acid), polyamides such as polycaprolactam, and block copolymers having both hydrophobic and hydrophilic groups. Other possible candidates include sodium dodecyl sulfate (SDS), sodium dodecylbenzyl sulfonate, polyacrylic acid derivatives, and the like. Further examples include amine-functionalized derivatives (e.g., polyamines, tertiary amines, or quaternary ammonium-functionalized derivatives), acid-functionalized derivatives thereof (e.g., carboxylic acid- or phosphonic acid-functionalized derivatives), such as amine-functionalized or amine-terminated polyalkylene oxides or acrylic polymers containing amine or acid functional groups. Other suitable dispersants include those known to those skilled in the art for use with carbon black, graphene, or carbon nanotubes. The composition can contain one dispersant or a mixture of two or more dispersants.
[0040] In one example, the dispersant belongs to a class that includes styrene-maleic anhydride resins and / or their derivatives, the latter being polymers made via the chemical reaction of styrene-maleic anhydride resins or prehydrolyzed styrene-maleic anhydride resins with small or large organic molecules having at least one reactive end group, such as an amine or epoxide group. Generally, this class of polymeric dispersants (also referred to herein as styrene-maleic anhydride-based) has a styrene-maleic anhydride copolymer backbone modified with various polymeric brushes and / or small molecules.
[0041] In another example, the dispersant includes PVP (of various molecular weights) or its derivatives, the latter generally referring to dispersants having a PVP backbone modified with small or large molecules through chemical reaction, etc. Examples of PVP-based dispersants include Ashland PVP K-12, K-15, K-30, K-60, K-90, and K-120 products, polyvinylpyrrolidone copolymers such as polyvinylpyrrolidone-co-vinyl acetate, and butylated polyvinylpyrrolidone such as Ganex™ P-904LC polymer.
[0042] In a further example, the dispersant is a cellulose-based dispersant, for example, comprising cellulose or a cellulose derivative, the latter having a cellulose backbone optionally modified with a small or large organic molecule having at least one reactive end group. In one specific example, the cellulose-based dispersant is typically a compound CMC (e.g., of various viscosities) prepared by the reaction of cellulose with chloroacetic acid. In another example, the dispersant is hydroxyethyl cellulose.
[0043] Many embodiments described herein use CNS-derived materials with CNT purity of 97% or greater. In many cases, the CNS used herein do not require additional additives to counteract van der Waals forces.
[0044] The CNS can be provided in the form of a loose particulate material (e.g., as CNS flakes, granules, pellets, etc.), or in a formulation that also includes a liquid medium, such as a dispersion, slurry, paste, or other form. In many embodiments, the utilized CNS is separated from its growth substrate.
[0045] In some embodiments, the CNS is provided in the form of flake material after removal from the growth substrate on which the carbon nanostructures were initially formed. As used herein, the term "flake material" refers to discrete particles having finite dimensions. For example, FIG. 3A shows an illustrative view of CNS flake material after isolation of the CNS from the growth substrate. The flake structure 100 can have a first dimension 110 ranging from about 1 nm to about 35 microns in thickness, particularly from about 1 nm to about 500 nm in thickness, including any value therebetween and any fraction thereof. The flake structure 100 can have a second dimension 120 ranging from about 1 micron to about 750 microns in height, including any value therebetween and any fraction thereof. The flake structure 100 can have a third dimension 130 ranging from about 1 micron to about 750 microns, including any value therebetween and any fraction thereof. Two or all of the dimensions 110, 120, and 130 can be the same or different.
[0046] For example, in some embodiments, second dimension 120 and third dimension 130 can independently be on the order of about 1 micron to about 10 microns, or about 10 microns to about 100 microns, or about 100 microns to about 250 microns, about 250 to about 500 microns, or about 500 microns to about 750 microns.
[0047] The CNTs within a CNS can vary in length from about 10 nanometers (nm) to about 750 microns (μm) or more. Thus, CNTs can be sized between 10 nm and 500 nm, 10 nm and 100 nm, 10 nm and 750 nm, 10 nm and 1 micron, 10 nm and 1.25 microns, 10 nm and 1.5 microns, 10 nm and 1.75 microns, 10 nm and 2 microns, or 100 nm and 500 nm, 100 nm and 750 nm, 100 nm and 1 micron, 100 nm and 1.25 microns, 100 nm and 1.5 microns, 100 nm and 1.75 microns, 100 nm and 2 microns, 500 nm and 750 nm, 500 nm and 1 micron, 500 nm and 1 micron, 500 nm and 1 micron, 500 nm and 1.25 microns, 500 nm and 1. 5 microns, 500 nm to 1.75 microns, 500 nm to 2 microns, 750 nm to 1 micron, 750 nm to 1.25 microns, 750 nm to 1.5 microns, 750 nm to 1.75 microns, 750 nm to 2 microns, 1 micron to 1.25 microns, 1.0 micron to 1.5 microns, 1 micron to 1.75 microns, 1 micron to 2 microns, or 1.25 microns to 1.5 microns, 1.25 microns to 1.75 microns, 1 micron to 2 microns, or 1.5 to 1.75 microns; 1.5 to 2 microns, or 1.75 to 2 microns. In some embodiments, at least one of the CNTs has a length of 2 microns or more, e.g., up to 4 microns or more, as determined by SEM.
[0048] Figure 3B shows an SEM image of an exemplary carbon nanostructure obtained as flake material. The carbon nanostructure shown in Figure 3B exists as a three-dimensional microstructure due to the entanglement and cross-linking of its highly aligned carbon nanotubes. The aligned morphology reflects the formation of carbon nanotubes on a growth substrate under rapid carbon nanotube growth conditions (e.g., several microns / second, e.g., about 2 microns / second to about 10 microns / second), resulting in substantially perpendicular carbon nanotube growth from the growth substrate. Without being bound by any theory or mechanism, it is believed that the rapid carbon nanotube growth rate on the growth substrate may contribute, at least in part, to the complex structural morphology of the carbon nanostructures. Additionally, the bulk density of the carbon nanostructures can be altered to some extent by adjusting the carbon nanostructure growth conditions, including, for example, by varying the concentration of transition metal nanoparticle catalyst particles disposed on the growth substrate to initiate carbon nanotube growth.
[0049] The flake structures may comprise a webbed network of carbon nanotubes in the form of a carbon nanotube polymer (i.e., "carbon nanopolymer") having a molecular weight within the range of about 15,000 g / mol to about 150,000 g / mol, including all values therebetween and any fraction thereof. In some cases, the upper end of the molecular weight range may be higher, including about 200,000 g / mol, about 500,000 g / mol, or about 1,000,000 g / mol. Higher molecular weights may be associated with carbon nanostructures of longer dimensions. Molecular weight may also be a function of the primary carbon nanotube diameter and the number of carbon nanotube walls present within the carbon nanostructure. The crosslink density of the carbon nanostructure may be greater than about 2 mol / cm. 3 ~about 80mol / cm 3The crosslink density can be in the range of 0.01 to 0.01. Typically, the crosslink density is a function of the carbon nanostructure growth density on the surface of the growth substrate, the carbon nanostructure growth conditions, etc. It should be noted that a typical CNS structure containing a large number of CNTs held in an open web-like arrangement eliminates or reduces the effect of van der Waals forces. Because this structure is more easily peelable, the many additional steps required to separate it or break it into branched structures make it unique and different from regular CNTs.
[0050] In the web-like morphology, the carbon nanostructures have a relatively low bulk density, e.g., about 0.005 g / cm 3 ~about 0.1g / cm 3 , or about 0.01 g / cm 3 ~about 0.05g / cm 3 The as-produced carbon nanostructures may have a density of about 0.003 g / cm 3 ~Approx. 0.015g / cm 3 Upon further consolidation and / or coating to produce carbon nanostructure flake material or similar morphology, the initial bulk density may be in the range of about 0.1 g / cm 3 ~Approx. 0.15g / cm 3 In some embodiments, optional further modifications of the carbon nanostructures can be performed to further alter the bulk density and / or other properties of the carbon nanostructures. In some embodiments, the bulk density of the carbon nanostructures can be further modified by forming a coating on the carbon nanotubes of the carbon nanostructures and / or by infiltrating various materials into the carbon nanostructures. Coating the carbon nanotubes and / or infiltrating the carbon nanostructures can further tailor the properties of the carbon nanostructures for use in various applications. Additionally, forming a coating on the carbon nanotubes desirably allows for easier handling of the carbon nanostructures. In some embodiments, further compaction can be performed to achieve a bulk density of about 1 g / cm. 3It is possible to increase the bulk density to an upper limit of 1.2 g / cm by chemically modifying the carbon nanostructure. 3 rises to the upper limit of
[0051] In addition to the flakes described above, the CNS material can be provided as granules, pellets, or other forms of loose particulate material, with typical particle sizes ranging from about 1 mm to about 1 cm, e.g., from about 0.5 mm to about 1 mm, from about 1 mm to about 2 mm, from about 2 mm to about 3 mm, from about 3 mm to about 4 mm, from about 4 mm to about 5 mm, from about 5 mm to about 6 mm, from about 6 mm to about 7 mm, from about 7 mm to about 8 mm, from about 8 mm to about 9 mm, or from about 9 mm to about 10 mm.
[0052] Commercially, examples of available CNS materials are those developed by Applied Nanostructured Solutions, LLC (ANS) (Massachusetts, United States).
[0053] As used herein, CNSs can be identified and / or characterized by a variety of techniques. For example, electron microscopy, including techniques such as transmission electron microscopy (TEM) and scanning electron microscopy (SEM), can provide information regarding characteristics, such as the frequency of the specific number of walls present, branching, the absence of catalyst particles, etc. See, e.g., Figures 2A-2B.
[0054] Raman spectroscopy can identify bands associated with impurities, such as the D band (1350 cm -1 near 1580 cm ) is related to amorphous carbon and the G band ( -1 The G' band (near 2700 cm) is associated with crystalline graphite or CNTs. -1 The CNS and CNT structures may be distinguishable by thermogravimetric analysis (TGA).
[0055] The conductive ink can include carbon nanostructures suspended in a suitable liquid vehicle. The loading of CNS and / or CNS-derived material in the liquid vehicle can be up to 5 or 10% by weight, e.g., 0.01% to 10%, 0.05% to 9%, 0.1% to 8%, 0.5% to 7%, or 1% to 5%. The CNS-derived material can be present in the conductive ink in an amount sufficient to result in a conductive coating (after printing and drying / curing) having the CNS-derived material present in an amount of 0.05% to 30% by weight (dry basis), e.g., 0.1% to 20%, 0.5% to 10%, or 0.75% to 5% by weight. The vehicle can be a polar fluid, e.g., water or an aqueous vehicle having at least 50% water by weight. Alternatively, the vehicle may be or include an organic solvent, such as a low molecular weight (e.g., C1-C10) hydrocarbon or aromatic substance, such as alcohol, aldehyde, ketone, and ether, dioxane, acetic acid, propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), dimethoxyethane, formic acid, acetonitrile, 1,4-dioxane, tetrahydrofuran, dimethylformamide, dimethylacetamide, n-methylpyrrolidone, chlorobenzene, trichlorobenzene, trichloroethylene, or ethylene glycol. Examples of alcohols include methanol, ethanol, isopropanol, perfluoropropanol, 2-methylpropan-1-ol, 1-butanol, 2-butanol, 2-butoxyethanol, 2-(2-butoxyethoxy)ethanol, and octanol. Examples of aldehydes include formaldehyde, acetaldehyde, propionaldehyde, and glutaraldehyde. Examples of ketones include acetone, methyl ethyl ketone, methylpentan-2-one, and diethyl ketone. Examples of esters include methyl acetate, ethyl acetate, and butyl benzyl phthalate.Examples of hydrocarbons include hexane, heptane, octane, nonane, and decane, dichloromethane, chloroform, 1,1,1-trichloroethane, trichloroethylene, isophorone, 2-nitropropane, tetrachloroethylene, naphtha, and acetonitrile. Examples of aromatics include benzene, toluene, xylene, 1,2,4-trimethylbenzene, phenol, and naphthalene. Mixtures of two or more of these solvents may also be used.
[0056] Any suitable dispersing agent may be used to improve the dispersion and suspension of CNS and other CNS-derived materials in the vehicle. Dispersing agents may include surfactants, functionalized polymers, and oligomers. Dispersing agents may be nonionic or ionic, including both anionic and cationic dispersing agents. Dispersing agents may be amphiphilic and may be polymeric or contain polymeric groups. Specific examples of polymeric dispersing agents include synthetic polymeric dispersing agents. Suitable molecular groups that may be included in dispersing agents include, but are not limited to, polyalkylene oxides, such as polyethylene oxide, polypropylene oxide, and mixtures and copolymers thereof; polyesters, such as polycaprolactone, polyvalerolactone, poly(hydroxystearic acid), and poly(hydroxyoleic acid); polyamides, such as polycaprolactam; polyacrylates; polyvinylpyrrolidone; and block copolymers containing both hydrophilic and hydrophobic groups. Other examples include amine-functionalized derivatives of any of these (e.g., polyamine, tertiary amine, or quaternary ammonium-functionalized derivatives), such as amine-functionalized or amine-terminated polyalkylene oxides containing amine or acid functionality (e.g., Jeffamine dispersants available from Huntsman), or acrylic polymers. Ethoxylates, such as alkylphenol ethoxylates and alkyl ethoxylates, are commonly used as dispersants in aqueous formulations. Examples include PETROLITE dispersants from Baker Petrolite. Other polymers and related materials that can be used as dispersants and additives in conductive inks include Tego products from Evonik, Ethacryl products from Lyondell, Joncryl polymers and EFKA dispersants from BASF, Solsperse™ dispersants available from Lubrizol, and Disperbyk® and Byk® dispersants from BYK. Any of the dispersants described above in the context of coatings for CNS can additionally or alternatively be used as dispersants in conductive inks.
[0057] The conductive ink may further include a conductive or non-conductive additive. Conductive additives include silver, copper, gold, platinum, palladium, ruthenium, copper, nickel, zinc, conductive oxides, or other conductive particles, and may be present in an amount of 0 to 99% by weight on a dry basis, e.g., 1 to 90%, 5 to 80%, 10 to 70%, 20 to 60%, 30 to 50%, 40 to 75%, or 50 to 95% by weight. The conductive additive is generally particulate and may have any shape suitable for use in conductive inks, such as spheres, flakes, rods, or wires. The conductive additive may have any size suitable for use in conductive inks, such as 100 or 200 nm, or up to hundreds of nanometers or tens of microns. The conductive ink may further include functional materials such as stabilizers, antioxidants, adhesion promoters, viscosity modifiers, etc. that improve the shelf life and printability of the ink.
[0058] The conductive ink may further comprise a binder. The binder may be a polymer, a monomer, or an oligomer. After printing and curing of the ink, the cured binder may be a thermosetting or thermoplastic polymer. Suitable polymers are those that can form gels in a liquid vehicle, such as poly(lactic acid), polystyrene, poly(methyl acrylate), poly(methyl methacrylate), poly(n-butyl acrylate), poly(2-hydroxyethyl methacrylate), poly(glycidyl methacrylate), poly(acrylic acid), poly(NN-dimethylacrylamide), poly(1-vinylanthracene), poly(2-vinylpyridine), poly(4-vinylpyridine), poly(N-vinylcarbazole), poly(N-vinylcarbonate ... The polymerizable monomer or oligomer may be selected from the group consisting of methyl methyl methacrylate (MMA), ...Suitable polymers that may be present in the coating after curing of the conductive ink include, but are not limited to, polyalkylenes, polyalkylene glycols, polyalkylene alcohols, polyacryloyl compounds, polyalkylene glycols, polyalkylene esters, polyolefins, vinyl polymers, alkoxylates, alkylolamides, esters, amine oxides, alkyl polyglucosides, alkylphenols, aryl alkyl phenols, polyvinyl alcohols, copolymers of polyvinyl alcohol and polyvinyl acetate, polyvinyl pyrrolidone, cellulose, starch, gelatin. , gelatin derivatives, amino acid polymers, polylysine, polyaspartic acid, polyacrylate, polyethylene sulfonate, polystyrene sulfonate, polymethacrylate, condensation products of aromatic sulfonic acid and formaldehyde, naphthalene sulfonate, lignosulfonate, copolymers of acrylic monomers, polyethyleneimine, polyvinylamine, polyallylamine, poly(2-vinylpyridine), block copolyethers, block copolyethers having polystyrene blocks and / or polydiallyldimethylammonium chloride, and copolymers or mixtures thereof. Specific examples of polymers include polyethylene, polypropylene, chlorinated polypropylene, polyvinyl alcohol, polyvinyl acetate, polyacrylate, polymethacrylate, cellulose polysaccharide, polystyrene, and mixtures or copolymers thereof.
[0059] The coating resulting from printing and curing the conductive ink can have any suitable thickness, for example, from 0.1 micron to 100 microns, e.g., from 0.5 micron to 80 microns, from 1 micron to 50 microns, from 5 microns to 30 microns, from 10 microns to 70 microns, from 30 microns to 60 microns, or from 50 microns to 90 microns.
[0060] The conductive ink is printed and cured to produce a coating that -6 ~10 14 ohm·cm, e.g., 10 -5 ~5×10 13 , 10-4 ~10 13 , 10 -3 ~5×10 12 , 10 -2 ~10 12 , 0.1 to 5 × 10 11 ohm·cm, 1 to 10 6 ohm·com, at most 0.1 ohm·cm, at most 1 ohm·cm, at most 10 ohm·cm, at most 100 ohm·cm, at most 10 4 ohm·cm, at most 10 6 ohm·cm, 10 6 ~10 10 ohm.com, 10 10 ~10 12 ohm·cm, or 10 12 ~10 14 Alternatively or additionally, the coating may have a volume resistivity of 10 ohm·cm. -6 ~10 14 Ohms / sq, e.g., 10 -5 ~5×10 13 , 10 -4 ~10 13 , 10 -3 ~5×10 12 , 10 -2 , 10 12 , 0.1 to 5 × 10 11 Ohms / sq, 1-10 6 ohms·com, at most 0.1 ohms / sq, at most 1 ohm / sq, at most 10 ohms / sq, at most 100 ohms / sq, at most 10 4 ohms / sq, at most 10 6 Ohms / sq, 10 6 ~10 10 ohm.com, 10 10 ~10 12 ohms / sq or 10 12 ~10 14 It may have a surface resistivity of ohms / sq.
[0061] The coating obtained by printing, particularly screen printing, and curing the conductive ink has a resistance of at least 300 volts under an applied voltage, for example, a voltage of 5 to 45 V. o F (149°C), e.g., 300o F(149℃)~600 o That is, the coating can achieve such temperatures when a voltage of 5 to 45 V is present. For example, the coating can achieve temperatures of at least 300°F (316°C) when a voltage of 40 V is present. o F (149°C), e.g., 300 o F(149℃)~600 o Temperatures of 316°C (100°F) can be achieved.
[0062] The present invention will be further clarified by the following examples, which are intended to be merely exemplary in nature. [Example]
[0063] Example 1 Conductive inks were prepared according to the formulations in Table 1 using various amounts of polyethylene glycol-coated carbon nanostructures (CNS) (Applied Nanostructured Solutions, Boston, MA) (Cabot Corporation, Boston MA). First, a thermoplastic resin binder solution was prepared. Pearlstick™ 5715 thermoplastic polyurethane elastomer (TPU) was dissolved in diethylene glycol monoethyl ether acetate solvent to form a 25% solids binder solution. The corresponding amount of CNS was added to the resin solution and mixed in a Speedmixer DAC 600.2 VAC (FlackTek) to form a thick paste. The pastes of Examples 1A, 1B, and 1C can also serve as CNS masterbatches, allowing for further letdown to reduce loading.
[0064] The ink was screen printed onto Kapton polyimide film (136-137 microns thick) and cured at 160°C for 10 minutes. The screen-printed template was 100 mm long and 1 mm wide. Resistivity was measured on a 60 mm segment of the printed ink using a Fluke 45 multimeter according to ASTM F1896-16 test procedure. The results are shown in Table 1.
[0065] Flexibility (Crease) Test: A substrate with a 100 mm printed line was folded in half so that the two halves of the line were touching (inner crease). The crease was creased by rolling an 1840 g circular weight across the crease and then rolling it again in the opposite direction. The substrate was then opened and folded in half in the opposite direction along the crease (outer crease), and the weight was again rolled back and forth. The substrate was then opened flat and the resistivity was measured as described above.
[0066] [Table 1]
[0067] Example 2 Carbon inks were obtained by dilution (letdown) of the sample prepared in Example 1. Table 2 shows letdown formulations obtained by diluting the formulation of Example 1A to 0.1% to 2% CNS loading. The inks prepared in Example 2 were screen printed, dried, and characterized using the same methods as described in Example 1. An optical micrograph of the printed ink of Example 2B is shown in Figure 4 (scale bar = 1 mm).
[0068] [Table 2]
[0069] Example 3 (Comparative Example) Table 3 shows comparative examples containing single-walled CNTs, multi-walled CNTs, and carbon black with an iodine value of 253 mg / g and an oil adsorption number of 192 mL / 100 g. The 25% TPU resin dispersed in diethylene glycol monoethyl ether acetate solvent from Example 1 was used as the binder solution, and sample preparation and analysis were performed as described in Example 1. Additional solvent was added to Example 3E to reduce the viscosity of the ink paste.
[0070] [Table 3]
[0071] Example 4 (Comparative) Silver inks were prepared according to the formulations listed in Table 4. 50 Silver flakes having the formula were used in Ag-based ink formulations. The inks were prepared, screen printed onto Kapton polyimide films, and cured as described in Example 1 to form coatings with various amounts of silver. Resistivity and flexibility were characterized as described in Example 1.
[0072] [Table 4]
[0073] Example 5 Conductive ink compositions were prepared using a mixture of Ag flakes and CNS or a mixture of carbon black and CNS as the conductive filler, as shown in Table 5. The ink formulations were prepared, screen-printed, and characterized as described in Example 1. The results show that even at only 70% silver loading, the use of 1 wt.% CNS results in a surface resistivity in the range of 0.1-0.2 ohm / sq at a thickness of 17 μm, a ten-fold decrease compared to the ink composition containing only 70% Ag (Example 4B). Furthermore, replacing 5 wt.% silver with 1 wt.% CNS maintains the resistivity performance of an 80% silver loading (Example 5B vs. Example 4C).
[0074] The combination of CNS (4%) and carbon black B (20%) in formulation 5C also significantly improved the electrical conductivity of ink formulation 3F with 20% carbon black B. The VR decreased from 1-10 ohm·cm (Example 3F) to approximately 0.1 ohm·cm (Example 5D), increasing the conductivity of the carbon ink.
[0075] [Table 5]
[0076] Example 6 Heating elements were printed using the inks prepared in the above examples by screen printing six layers of ink onto a substrate to create a heating element approximately 20-30 microns thick. A schematic of the heating element structure is shown in Figure 5. Carbon ink 60 was printed onto substrate 61 to create a rectangle 1.2 cm long (L) and 1.0 cm wide (W) (Figure 5A). Silver ink prepared according to Example 4D was used to form bus bars 62, or electrodes, to provide connection to a power source 64, leaving a 1 cm x 1 cm carbon ink rectangle (Figure 5B). A TENMA® 72-7295 DC regulated power supply was used as power source 64 to heat up the printed heating element (Figure 5C). Once the heater reached steady state, the temperature profile was measured using a FLIR T620 thermal imaging camera 66. The carbon element heated up rapidly. The heater was considered "steady" when no significant temperature increase was observed at a given voltage.
[0077] Table 6 shows the heating performance of heating elements printed from ink formulations selected from Examples 1, 2, and 3. The CNS-based coatings achieved higher temperatures than the carbon black-based coatings at voltages above 10 V, and also achieved higher temperatures than the carbon black-based coatings at voltages above 100 V. o The results show that the voltage required to achieve temperatures above F is lower than for carbon black-based coatings.
[0078] [Table 6]
[0079] The foregoing description of preferred embodiments of the present invention has been presented for purposes of illustration and description. It is not intended to be exhaustive or to limit the invention to the precise form disclosed. Modifications and variations are possible in light of the above teachings or may be acquired from practice of the invention. The embodiments have been chosen and described in order to explain the principles of the invention and its practical application so that those skilled in the art may utilize the invention in various embodiments with various modifications suited to the particular uses contemplated. It is intended that the scope of the invention be defined by the claims appended hereto and their equivalents.
Claims
1. A conductive ink comprising 0.05% to 30% by weight (dry basis) of at least one CNS-derived material selected from the group consisting of carbon nanostructures, carbon nanostructure fragments, and crushed carbon nanotubes in a liquid vehicle, and a binder.
2. 10. The conductive ink of claim 1 having 0.1% to 20%, 0.5% to 10%, or 0.75% to 5% by weight of CNS-derived material.
3. 3. The conductive ink of claim 1 or 2, wherein the ink comprises 0.01 to 10 wt. % CNS-derived material, based on the total mass of the conductive ink.
4. 4. The conductive ink of claim 3, wherein the ink comprises 0.05% to 9% by weight, 0.1% to 8% by weight, 0.5% to 7% by weight, or 1% to 5% by weight of CNS-derived material, based on the total mass of the conductive ink.
5. A conductive ink according to any preceding claim, wherein the liquid vehicle comprises an organic solvent, water, or both.
6. The conductive ink of any one of claims 1 to 5, wherein the binder comprises a polymer, a monomer, an oligomer, or a blend of two or more thereof.
7. The conductive ink of any one of claims 1 to 6, further comprising a dispersant.
8. The conductive ink of claim 7 , wherein the dispersant is a non-ionic dispersant, an anionic dispersant, or a cationic dispersant.
9. 9. The conductive ink of claim 1, further comprising one or more additives selected from a conductive additive, a stabilizer, an antioxidant, an adhesion promoter, and a viscosity modifier.
10. 10. The conductive ink of claim 9, wherein the additive is a conductive additive selected from silver, copper, gold, platinum, palladium, ruthenium, copper, nickel, zinc, and conductive oxides.
11. 11. The conductive ink of claim 9 or 10, wherein the conductive additive is in the form of a sphere, flake, rod, or wire.
12. 12. A conductive ink according to any one of claims 9 to 11, wherein the conductive additive is present in an amount of 0 to 99% by weight on a dry basis, such as 1% to 90% by weight, 5% to 80% by weight, 10% to 70% by weight, 20% to 60% by weight, 30% to 50% by weight, 40% to 75% by weight, or 50% to 95% by weight.
13. When screen printed and cured, the resulting coating has a resistivity of at least 300 under an applied voltage of 40 V. ° 13. The conductive ink of claim 1, which achieves a temperature of 149°C.
14. 10. The conductive ink of claim 1 further comprising up to 85% (dry basis) metallic particulate, wherein when screen printed and cured, the resulting coating has a lower surface resistivity than a coating having the same composition but without the CNS-derived material.
15. The conductive ink of claim 5, wherein the conductive ink comprises 65% to 83% metallic particulate.
16. A substrate printed with a conductive ink according to any one of claims 1 to 15, wherein the ink is cured.
17. 17. The substrate of claim 16, wherein the cured ink has a thickness of from 0.1 microns to 100 microns, e.g., from 0.5 microns to 80 microns, from 1 micron to 50 microns, from 5 microns to 30 microns, from 10 microns to 70 microns, from 30 microns to 60 microns, or from 50 microns to 90 microns.
18. The cured ink is -6 ~10 14 Ohm cm, e.g., 10 -5 ~5×10 13 , 10 -4 ~10 13 , 10 -3 ~5×10 12 , 10 -2 ~10 12 , 0.1 to 5×10 11 Ohm cm, 1 to 10 6 ohm-com, at most 0.1 ohm-cm, at most 1 ohm-cm, at most 10 ohm-cm, at most 100 ohm-cm, at most 10 4 ohm-cm, at most 10 6 ohm cm, 10 6 ~10 10 ohm.com, 10 10 ~10 12 ohm-cm or 10 12 ~10 14 18. The substrate of claim 16 or 17, having a volume resistivity of ohm-cm.
19. The cured ink is -6 ~10 14 Ohms / sq, e.g. 10 -5 ~5×10 13 , 10 -4 ~10 13 , 10 -3 ~5×10 12 , 10 -2 ~10 12 , 0.1 to 5×10 11 Ohms / sq, 1-10 6 ohms.com, at most 0.1 ohms / sq, at most 1 ohm / sq, at most 10 ohms / sq, at most 100 ohms / sq, at most 10 4 Ohms / sq, at most 10 6 Ohms / sq, 10 6 ~10 10 ohm.com, 10 10 ~10 12 Ohms / sq or 10 12 ~10 14 The substrate according to any one of claims 16 to 18, having a surface resistivity of ohms / sq.
20. The substrate of any one of claims 16 to 19, wherein the substrate comprises fabric, paper, wood, metal, glass, ceramic, concrete, polymer, or a mixture or composite of two or more thereof.
21. 21. The substrate of claim 20, wherein the substrate comprises a polyolefin, a polyimide, a polyester, a polyurethane, or a vinyl polymer.
22. 22. The substrate of claim 20 or 21, wherein the substrate comprises polyethylene, polyethylene terephthalate, polyvinyl chloride, or polystyrene.
23. The substrate according to any one of claims 16 to 22, wherein the substrate is a film, a woven fabric, or a nonwoven fabric.
Citation Information
Patent Citations
Carbon nanotube-containing coating
JP2004526838A
Exothermic body using fine carbon fiber, and manufacturing method thereof
JP2010045025A
Electron emission element and method of manufacturing cathode electrode of the same
JP2011181351A
Active energy ray-curable nanocarbon dispersion, method for manufacturing the same, and active energy ray-curable coating agent using the same
JP2014152080A
Mixtures, methods, and compositions relating to conductive materials
JP2015518063A